Menstrual pattern of Adolescence - Selvalakshmi S,; Lakshmanan S, (The Bioscan, 2024)
OBJECTIVE: This analysis helps to find out the pattern of menstruation among college students in Tamilnadu India. Materials and Methods: In this cross-sectional study, a survey was conducted in various colleges in Dindigul District. These questionnaires were based on socioeconomic data, menarche, menstrual cycle flow, and their perception of menstruation. Results: The age of menarche was 77.7% of the students attaining earlier (9-12). Dysmenorrhea (65%), premenstrual syndrome (PMS) (71.2%), and irregular cycles (33.8%) were found to be common problems among teenagers. Conclusion: Adolescents need to be educated about menstrual health and menstrual disorder.